The failure of the 'single source of truth about Kenyans': The NDRS, collateral mysteries and the Safaricom monopoly. Issue 1 (2nd January 2019) - Breckenridge, Keith
ABSTRACT: This article explores the recent failure of an elaborate biometric registration scheme, the National Digital Registry System (NDRS), in Kenya. The article shows that the Kenyan and South African economies are closely linked in their obsessions with biometric identification registration, and financialisation, but it also draws out the particular significance, in the Kenyan case of a conflict over the form and ownership of credit information as collateral. The failure of the project was the result of fractured financial interests, and specifically of a conflict between the formal banks and Safaricom, the monopoly telecommunications firm that has created the globally distinctive system of mobile money, M-Pesa. At issue between them were two very different models for decision-making, and profit, in the extension of personal credit.